(untitled) (SETARA : Jurnal Ilmu Hukum, 2023)
This article examines the enforcement of criminal justice against the intentional and unauthorized distribution of electronic documents containing defamatory or insulting content. The issue is important because the expansion of information technology has made reputational harm easier to spread across digital networks, while legal responses must still balance freedom of expression, personal honor, and public order. Using normative juridical research with statutory and conceptual approaches, the article reviews the relationship between the Criminal Code and Law Number 11 of 2008 concerning Electronic Information and Transactions. The study finds that Article 27 paragraph (3) of the Electronic Information and Transactions Law functions as a specific legal basis for addressing digital defamation, yet its enforcement remains sensitive because interpretation of intent, unlawfulness, and dissemination can affect legitimate criticism and public discourse. The article concludes that effective justice requires careful proof of each element of the offense, proportional law enforcement, and greater public legal awareness regarding responsible use of electronic media.